Utilization of edutainment to improve understanding of biology concepts in high school students - Magdalena, Marini; Rahayu, Maya; Ganjar, Gigin; Almara, Listya (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Biology education in high school is often considered boring and difficult to understand by students. This can lead to low student interest and learning outcomes in biology subjects. Edutainment, which is a combination of education and entertainment, can be a solution to overcome these problems. Edutainment can help students learn biology in a more fun and interactive way, thereby improving understanding of biological concepts. This study aims to determine the effect of edutainment utilization on the understanding of biological concepts in high school students. The research method used was an experiment with a pretest-posttest group design. The research subjects were Xth grade high school students who were divided into two groups, namely the experimental group and the control group. The experimental group was given biology learning using edutainment, while the control group was given biology learning with traditional methods. The results showed that there was a significant difference between the biology learning outcomes of students in the experimental group and the control group. Students in the experimental group who were given biology learning using edutainment showed higher learning outcomes compared to students in the control group who were given biology learning with traditional methods. This shows that the use of edutainment can improve the understanding of biological concepts in high school students.